تنافسية القطاع السياحي في سورية (دراسة تحليلية وفق منهجية منتدى دافوس والمجلس العالمي للسياحة والسفر) - محمود, حبيب; شوباصي, شعبان (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يعد قطاع السياحة أحد القطاعات الاقتصادية الواعدة في سورية، حيث بلغت مساهمة اقتصاد السياحة والسفر في الناتج المحلي الإجمالي مبلغ /5.13/ مليار دولار لعام 2008 (14.5%)، لذلك فتطوير هذا القطاع أصبح قضية مهمة في ظل التنافس الكبير بين دول العالم في مجال تحسين قدراتها السياحية وابتكار أحدث الأساليب في تقديم المنتجات السياحية لتحقيق أكبر طلب سياحي ممكن. بناءً على ما تقدم جاء هذا البحث حتى يسلط الضوء على تنافسية القطاع السياحي في سورية من المنظور الكلي، متناولاً بالترتيب أهم الأفكار التي تخدم الموضوع وفقاً للمحاور التالية: 1. مفهوم التنافسية وأنواعها. 2. الجاذبية السياحية للقطاع السياحي السوري. 3. الجاذبية الاستثمارية للقطاع السياحي السوري. 4. مرونة القطاع السياحي السوري. 5. الاستنتاجات والتوصيات. The tourism sector is one of the promising economic sectors in Syria, the contribution of the economy of tourism & travel in GDP reached sum /5.13/ billions dollar (14.5%) in year 2008. So the developing of this sector became an important issue because of the big competition between countries on many sides such as improving the national tourism abilities, and creation the modish ways in presenting the touristic products to achieve the biggest possible touristic demand. Depending on the above-mentioned points, this paper has studied the following issues that serve the goals of the subject: 1- competitiveness Concept and types. 2- The tourism attraction of the Syrian tourism sector. 3- investment attraction of the Syrian tourism sector. 4- flexibility of the Syrian tourism sector. 5- Results and recommendations.